Implementasi Merdeka Belajar dalam Pembelajaran Bahasa Indonesia - Suci, Dende; Hajar, Siti; Hesti, Hesti (Primary Journal of Multidisciplinary Research, 2025)
The "Merdeka Belajar" Program initiated by the Ministry of Education, Culture, Research, and Technology aims to create a more flexible education system that is student-centered and relevant to current needs. In Indonesian language learning, this approach encourages teachers to design contextual, creative learning activities that focus on developing students' literacy, critical thinking, and communication skills. This research aims to analyze the application of "Merdeka Belajar" principles in teaching the Indonesian language, focusing on teaching methods, the use of technology, and student engagement in learning. The results show that the implementation of "Merdeka Belajar" enhances students' motivation and participation through the use of learning materials aligned with their interests and local culture, integration of digital technology, and project-based assessment. Thus, this approach positively impacts the mastery of Indonesian language competencies while preparing students to face global challenges. However, further support for teachers is needed to maximize the program's implementation, particularly in designing adaptive curricula and training on technology utilization